PEREKONOMIAN RUMAH TANGGA MUSLIM TERHADAP AKTIVITAS NERACA KEUANGAN RUMAH TANGGA - ALMIZAN ALMIZAN; TONY ISWADI (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2018)
The research themes are: financial balance. The purpose of the paper is to explain the balance sheet of Muslim households. This research is a research library research. Data analysis techniques are carried out by descriptive analysis. The balance between income and expenditure in Muslim households is the basis for the household economy, so as to avoid problems that occur in the future. Preparation of the balance sheet of the household budget is data that contains certain boundaries and estimates in terms of income, expenditure and development of funds so that it can estimate funds and be able to overcome the problem of lack of funds.